Burden of Care of Various Infant Orthopedic Protocols for Improvement of Nasolabial Esthetics in Patients With CUCLP. (October 2018) - Singer, Emily; Daskalogiannakis, John; Russell, Kathy A.; Mercado, Ana M.; Hathaway, Ronald R.; Stoutland, Alicia; Long, Ross E.; Fessler, Jennifer; Semb, Gunvor; Shaw, William C.
Objectives: 1. To evaluate the orthodontic burden of care of nasoalveolar molding (NAM) and modified McNeil for the treatment of patients with complete unilateral cleft lip and palate (CUCLP). 2. To compare the esthetic outcomes of each with those of centers not utilizing infant orthopedics (IO). Design: Retrospective cohort study. Setting: Institutional. Participants: Four cohorts with repaired CUCLP (n = 149) from 3 centers. Interventions: Two cohorts were treated in the same center and had either traditional infant orthopedics (TIO) or NAM and 2 were treated in centers not employing IO. Main Outcome Measures: Burden of care data for the IO groups were compared using t tests. Frontal and profile photographs at approximately age 5 were collected for ratings of nasolabial esthetics, using a modification of the Asher-McDade method. Intrarater and interrater reliabilities were determined using weighted κ statistics. Median ratings were compared using a Kruskal-Wallis test. Results: The burden of care of NAM was significantly greater than TIO for both the number of visits (9.9 vs 6.6, [ P < .001]); and treatment duration (127 vs 112 days, [ P < .05]). Significant differences in nasolabial esthetic ratings were noted among the 3 centers. No significant differences were observed in the nasolabial esthetic outcomes between the NAM and TIO groups. Conclusions: 1. NAM required more visits and longer overall duration compared with TIO. 2. The center employing IO showed favorable nasolabial esthetics compared to those not utilizing IO. 3. No significant differences were found in the nasolabial esthetics of patients who have received NAM compared with TIO.